Production of Dried Yoghurt Starter Using Foam-Mat Drying Method: Effect of Egg White Foam Addition on Physical and Chemical Characteristics - Elok Zubaedah; Joni Kusnadi; Ima Andriastuti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Yoghurt starter is usually prepared, preserved, and sold in liquid form which required special treatment. Drying is an alternative process to provide starter culture. Problem in using drying method is longer time so that the viability cell culture is low. In this experiment foam-mat drying method was used to produce dried starter culture. Addition of egg white to the starter media is expected to shorten the drying time, so and improve the viability of cell culture. This research used of randomised bock design and using addition of egg white foam as a treatment. The treatment consisted of 6 level with concentration of white egg of 0,510,15,20 and 25% and vacuum dried at 50C. The result showed that the best treatment was yoghurt starter prepared with addition of 15 % egg white foam, based on the parameters as follow : Total Lactic Acid Bacteria : 1,5 105 cfu/g, Total Lactobacillus 1,5. 104 cfu/g, total yeast and mold : 1.6 104 cfu/g, drying time 3,16 hr, pH 4,5 total acidity 0,82%. Key words : Yoghurt, egg white, foam, drying method.